Understanding the religious rights of the Muslims in the Philippines: a catalyst for peace and justice Kefahaman tentang hak beragama orang Islam di Filipina: pemangkin untuk keamanan dan keadilan - Tagaranao, Mariam Saidona; Gamon, Alizaman Dumangcag (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Religious rights for minorities are not merely a privilege policy but an important commitment that should be acknowledged by any organization, state or nation. The contemporary legal systems of the world recognize religious rights particularly in today’s multicultural societies. This system has been acknowledged by the international law of human rights and the United Nations Conventions. Religious faith and religious practices are inherently protected by the Constitution of the Republic of Philippines. International law of human rights becomes the basis for a non-Muslim government to provide commitments in promoting spiritual and conventional infrastructures for Muslim minorities. The main objective of this paper is to discuss the national laws that can accommodate Muslim religious rights based on how Islam defines it, in order to achieve a lasting peace in the Philippines. The paper recommends that the universal principle of peace must be contained in the legal reform of every sovereign nation. In addition, religious obligations and liberties must be fairly treated and regarded as a national agenda towards promoting peace and justice.